“Somewhere in their Middle” (Konturen, 2026)
Two years (and counting) after the centennial of Franz Kafka’s death, critical reflection on his work remains very much alive. This special issue of Konturen focuses on two major strands that continue to deepen and challenge our understanding of a writer whose prose has been the subject of so much extant writing already. These two broad approaches to Kafka’s work could be understood as sustaining each other in a diametrically opposed way.
Keywords: meaning; interpretation